Characteristics and Analysis of Factors Affecting the Performance of Service Providers (Contractors) in Denpasar City in 2023 - Ariana, I Komang Agus; Wirawan, Ni Putu Mirah Sukmadewi Putri; Kumara, I Nyoman Indra; Nuraga, I Ketut (PT FORMOSA CENDEKIA GLOBAL, 2024)
Contractors are individuals or business entities that have expertise in carrying out construction work in accordance with planning, where the appointment of contractors is mostly carried out through a tender/auction system (Sholeh, 2020). Nowadays, contractors are a business that is in great demand by the public, but the development of the quantity of construction service companies has not been followed by an increase in qualifications and performance. One of the reasons is that the business and expertise requirements (SKK) are still not met, which will later affect business reliability and competitiveness. (Priana, 2018). Seeing this situation, it is very important to research the characteristics and factors that affect the performance of service providers (contractors) in the city of Denpasar in 2023. The method used in this study is descriptive statistics as well as factor analysis is used to explain the factors that affect contractor performance. From the research that has been carried out, 1). Contractors in the city of Denpasar have good human resources, experience, finance, and equipment and are in accordance with Law No. 11 of 2020 concerning Job Creation and LPJK No. 3 of 2017 concerning Certification and Registration of Construction Implementation Services Business. 2). The most influential factor on contractor performance is in group I with a total diversity value of 32.756%.